Pengembangan Lembar Kerja Peserta Didik Elektronik berbasis Science, Technology, Engineering, and Mathematics untuk Meningkatkan Kreativitas Siswa SMP - Sri Wahyuni*; Pramudya Dwi Aristya Putra; Siti Anisa Hidayati (Universitas Syiah Kuala, 2022)
Electronic student worksheets or E-LKPD are teaching materials designed digitally to support the learning process based on science, technology, engineering mathematics or STEM to increase student creativity through project design, planning activity schedules or work plans. This study aims to develop a valid, practical, and effective STEM-based E-LKPD in increasing the creativity of junior high school students. The methodology used in this research is research and development (RD) with the ADDIE model, namely analysis, design, development, implementation, and evaluation. The analysis stage is to determine and define student needs through interviews with teachers and students. The design stage is done by designing a STEM-based E-LKPD that suits the needs in terms of design, language, and materials. The development stage is carried out by developing products that are validated by validators, namely material experts, media experts, and science subject teachers to determine the feasibility of the product. The implementation phase is a trial using STEM-based E-LKPD on student creativity. The evaluation stage is carried out with the final revision of the product developed in accordance with the input suggestions at the implementation stage. The results of the study can be concluded that the STEM-based E-LKPD on temperature and heat materials to increase the creativity of junior high school students shows results with valid, practical, and effective categories